2018
DOI: 10.1007/s13524-018-0705-4
|View full text |Cite
|
Sign up to set email alerts
|

Can Public Housing Decrease Segregation? Lessons and Challenges From Non-European Immigration in France

Abstract: Recent decades have seen a rapid increase in the share of non-European immigrants in public housing in Europe, which has led to concern regarding the rise of ghettos in large cities. Using French census data over three decades, we examine how this increase in public housing participation has affected segregation. While segregation levels have increased moderately, on average, the number of immigrant enclaves has grown. The growth of enclaves is being driven by the large increase in non-European immigrants in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…Third, limited spatial assimilation among immigrant descendants also provides fertile ground for future qualitative and survey-based research that can provide self-reported information on individuals’ residential preferences and experiences of blocked opportunities. Fourth, many immigrants live in social housing, which often increases ethnic residential segregation, possibly contributing to greater intergenerational persistence in disadvantaged and segregated neighborhood contexts (McAvay 2018; Verdugo and Toma 2018). This article lacked information on (parental) social housing or transition to homeownership, but future research should address how these factors shape immigrant descendants’ contextual mobility.…”
Section: Discussionmentioning
confidence: 99%
“…Third, limited spatial assimilation among immigrant descendants also provides fertile ground for future qualitative and survey-based research that can provide self-reported information on individuals’ residential preferences and experiences of blocked opportunities. Fourth, many immigrants live in social housing, which often increases ethnic residential segregation, possibly contributing to greater intergenerational persistence in disadvantaged and segregated neighborhood contexts (McAvay 2018; Verdugo and Toma 2018). This article lacked information on (parental) social housing or transition to homeownership, but future research should address how these factors shape immigrant descendants’ contextual mobility.…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with evidence of high residential segregation among non-European immigrants and their children (McAvay and Safi, 2018; Pan Ké Shon and Verdugo, 2015; Safi, 2009), ethnic clustering and the ‘native’ flight phenomenon (McAvay, 2018b; Rathelot and Safi, 2014), as well as ample evidence of discrimination in housing and labour markets targeting these groups (Bonnet et al, 2016; Bunel et al, 2017; Jacquemet, 2013; Safi and Simon, 2014; Simon and Kirszbaum, 2001). Past research also indicates that the strong concentration of non-European immigrants and their children in the public housing sector drives spatial segregation and disadvantage (Verdugo, 2011; Verdugo and Toma, 2018). Further, school segregation is prevalent, resulting in the concentration of minorities in lower-quality facilities with weaker educational performance (Felouzis, 2003; van Zanten, 2001), which could in turn negatively impact educational outcomes and labour market opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…Although less is known about segregation beyond the first generation, due to restrictions in census data, a few studies indicate that spatial inequalities are largely transmitted to the second generation, particularly among non-Europeans (McAvay 2018a, b;McAvay and Safi 2018). Immigrant segregation appears to be in part maintained by discrimination on the Parisian housing market (Bonnet et al 2016;Bunel et al 2017) as well as native flight dynamics out of immigrant areas (Rathelot and Safi 2014;McAvay 2018a, b), particularly in areas near large public housing projects (Verdugo and Toma 2018).…”
Section: The Role Of Immigrant Residential Segregationmentioning
confidence: 99%